Peran Sub-Sektor Perkebunan Terhadap Perekonomian di Kabupaten Ogan Komering Ulu - Iwan Kurniawan; Munajat; Yunita Sari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The research objective is to analyze the leading plantation commodities in Ogan Komering Ulu district, to analyze the position of the leading plantation commodities in the furure, to analyze changes in the position of plantation commodities in the current and future economy. Used Location Quotient (LQ), Dynamic Location Quotient (DLQ), Shift Share analysis, Overlay analysis and class typology. This study uses secondary data on plantation production from 2011-2020.From the results of the study, it was found that oil palm and coffee commodities were superior based on the results of Overlay analysis between (LQ), (DLQ), Shift Share of commodities that had advantages, namely rubber, rubber commodity class typology (Quadrant III) advanced but depressed sub-sector, coconut commodity palm, coconut, coffee, and cocoa (Quandran IV) the classification of potential sub-sectors is relatively lagging behind.